A COMPARATIVE ANALYSIS OF WOMEN EMPOWERMENT IN THE PAST AND THE 21ST CENTURY AFRICAN SOCIETY IN THE CONTEXT OFÌWÒRÌTÚRÚPỌ̀NIN IFÁ DIVINATION - SAMUEL KÁYỌ̀DÉ OLÁLẸ́YẸ; OLÚWÁTÓYÌN ADÉBÓ̩LÁ GBÀDÀMÓ̩S̩Í (International Studies Journal)
In the contemporary time, the mission of every country in the entire continent is to provide employment support for women who are in one disadvantaged position or the other. As a result of this, many programmes are designed to help in this capacity. However, looking at women empowerment from the past, can one really say that women are not empowered particularly in Africa and in Yorùbá society in Nigeria to be specific even from the time of the gods to the present time? This question is important because there were notable figures (women) in the history of the Yorùbá society then and now that were/are greatly empowered. Aje, the goddess of wealth in Ìwòrìtúrúpọ̀n, Ẹlẹ́kọdèrè in Ìrósùn Méjì, Ẹfúnṣetán Aníwúrà, the Ìyálóde Ibadan of her time, Ẹfúnroyè Tinúbú, Ayé the powerful rich lady of Adó Èkìtì just to mention a few were women that were greatly empowered. In fact, there were no women in the past who were not one way or the other empowered in various businesses. One may be tempted to ask, what is the missing link between the past and the present that necessitated the shout for the women empowerment today for the sake of future? Have all the programmes so designed been able to cater for women empowerment? These were the questions this paper tries to interrogate by interviewing 30 women, 20 men in the city of Ibadan and their opinions content analysed. The study revealed that empowerment is not new to African and the agitation thus, has foreign hands, and product of intellectual poverty considering the fact that the structure of African society is an organised one based on gender roles. The paper therefore, recommends that we should value where and how the Creator placed us rather than looking for what is not lost.